Le feste ittite del tuono Edizione critica di CTH 631 - BARSACCHI, FRANCESCO GIUSEPPE (Studia Asiana, 2017)
The book contains the philological edition of the corpus of Hittite texts currently collected under number 631 of the Catalogue des Textes Hittites by E. Laroche. They constitute the description of religious ceremonies celebrated in connection with the atmospheric phenomenon of thunder, interpreted as a manifestation of the god of the storm, which was the greatest divinity of the Hittite pantheon. The documents of major extension, presented with a transliteration and translation, are accompanied by a philological comment, aimed at highlighting their structure as well as lexical and grammatical peculiarities, and are introduced by an analysis of dating conducted on a palaeographic basis. The minor fragments are presented in transcription and, where possible, in translation. The text discusses the possible attribution of each fragment to the corpus, based on structure and content. The critical edition of the texts is preceded by an introductory chapter in which the nature of thunder-related festivities and their status in the Hittite cultural calendar are discussed.